Knowledge Applied Realistic Assessment (KARA) in Araling Panlipunan 8: Development and Validation - Castillo, Kirsha Kara (International Journal of Arts, Sciences and Education, 2025)
Knowledge Applied Realistic Assessment (KARA) for Araling Panlipunan 8 was crafted and validated. Assessment is based on the Most Essential Learning Competencies (MELCs) of the Department of Education. Traditional assessment sometimes focused on rote memorization rather than using practical assessment that promotes analysis, problem-solving as well as higher-order thinking skills. This study utilizes the Research and Development (R&D) wherein it needs a number test experts in the validation of the assessment tool. In addition, this study needs 30 Grade 9 students of Concepcion National High School to check its reliability. Knowledge Applied Realistic Assessment underwent a content validation with the use of Content Validity Index (CVI) and a series of reliability testing by employing Kuder-Richardson 20, Test-Retest, and Split-Half methods. The results indicated that KARA gained a perfect content validity score (S-CVI= 1.00), it affirms that the entire assessment tool measures the intended learning competencies in Araling Panlipunan 8 under the (MELCs). This study exhibited a strong internal consistency because it acquired a score ranging from 0.81 – 0.84 in KR-20 in all four quarters. The reliability statistics of KARA in test-retest produced a high correlation ranging from 0.88-0.97, which confirms that the assessment tool is reliable. In split-half method, KARA demonstrated an acceptable to good reliability across all four quarters. With these results, it suggests that KARA is a valid and reliable assessment tool in assessing students’ competence in analyzing, in interpreting and in applying knowledge in actual scenarios. This study promotes another innovative assessment that highlights the value of applying knowledge in Araling Panlipunan 8.